Systematic Review of Design-Based Research Progress: Is a Little Knowledge a Dangerous Thing?. (March 2013) - McKenney, Susan; Reeves, Thomas C.
Sufficient attention and resources have been allocated to design-based research (DBR) to warrant review concerning if and how its potential has been realized. Because the DBR literature clearly indicates that this type of research strives toward both the development of an intervention to address a problem in practice and empirical investigation yielding theoretical understanding that can inform the work of others, thoughtful assessment of DBR progress must devote substantial attention to each of these aspects. This requires an in-depth analysis of full-text reports of DBR, framed by a refined conceptualization of the intended outputs of DBR, and ideally, complemented by empirical investigation involving design-based research participants directly.